Bookseller as a cultural agent: book trade in Estonia in the second half of the 19th and at the beginning of the 20th century - Jantson, Signe; Reimo, Tiiu (Knygotyra, 2006)
The article handles general developments and changes in book trade which took place in Estonia during the second half of the 19th century. The aim is to show the formation of bookshops trading with Estonian books and to analyse the activities of Estonian booksellers.The survey is based on the research literature and on the master thesis by Signe Jantson "Raamatukaubandus Eestis aastatel 1850–1917: raamatukauplused ja nende omanikud" (Book trade in Estonia 1850–1917: bookshops and their owners) [9]. In this study, great importance was attached to the national and social origin of bookshop owners and their activities.Up to the middle of the 19th century, the book production and dissemination in Estonia was in the hands of Baltic German entrepreneurs and depended on the political and economic developments not only in Russia but also in Germany.In the middle of the 19th century, there were only 5 bookshops in Estonia located in bigger towns – Tallinn and Tartu. In 1870 the number of bookshops reached 13. The greater ascent can be noticed in the last decade of the period – 1870–1880 when 20 new bookshops were opened.In 1867 Heinrich Laakmann, a German origin publisher and the printing shop owner, opened the first bookshop in Tartu to sell Estonian language books. The economic and political reforms as well as the national awakening movement favoured the engagement of Estonians in the sphere of book production and dissemination. Increasing publishing of Estonian language books enabled the development of trade. At the end of the national awakening period most of the bookshop owners were already of Estonian origin.Since the 1870s the number of Estonian bookshops started to grow, and at the end of the 19th century they outnumbered German and Russian shops. All over Europe book trade concentrated into the big cities (in the case of Estonia, in Tallinn and Tartu), but bookshops were opened also in the rural area (small towns and villages).Altogether 263 bookshops were founded in the second half of the 19th and at the beginning of the 20th century, and 283 persons became bookshop owners (at least for some years). These figures allow to conclude that book trade was a popular sphere of activity. The most intensive foundation of bookshops occurred during 1898–1904.
Keywords: -